The Influence of School Fees, Age, Gender on Children’s Education Level in Indonesia - Dian Isnawati; Maimun Sholeh (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This study aims to determine the effect of school fees, age and gender on children’s education level in Indonesia. Variables in school fees are school fees, equipment and transportation. The age variable is the sample that is aged 15 to 25 years. Gender variables consist of male and female. This study uses secondary data from the Indonesian Family Life Survey 5 (IFLS 5). The sample in this study were 2,601 respondents. It employs regression analysis and quantitative approach. It proves that there is a significant effect between school fees, age and gender on children's education levels.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh biaya sekolah, usia, dan jenis kelamin terhadap tingkat pendidikan anak di Indonesia. Variabel biaya sekolah adalah biaya bersekolah, peralatan sekolah dan transportasi. Variabel umur adalah sampel yang berumur 15 sampai 25 tahun. Variabel gender terdiri dari laki laki dan perempuan. Penelitian ini menggunakan data sekunder dari Indonesian Family Life Survey 5 (IFLS 5). Sampel pada penelitian ini sebanyak 2.601 responden. Penelitian ini menggunakan analisis regresi dan pendekatan kuantitatif. Analisis ini membuktikan ada pengaruh yang signifikan antara biaya sekolah, usia dan jenis kelamin terhadap tingkat pendidikan anak.